A nacre-inspired strong and flame retardant laminated veneer lumber bonded with magnesium oxychloride cement. Issue 1 (2nd January 2023) - Sun, Xinyan; Ye, Qianqian; Shi, Sheldon Q.; Gong, Shanshan; Gao, Qiang; Li, Jianzhang; Fang, Zhen
ABSTRACT: Laminated veneer lumber (LVL) is a novel artificial wood board that can make full use of small-diameter logs, however, problems such as low strength and inflammable property have limited its applications in architecture. Inspired by the "brick and mortar" structure of nacre, a new type of LVL was developed, in which magnesium oxychloride cement (MOC) was used as the substitute of traditional adhesives and D-gluconic acid sodium salt was employed as a water-resistant modifier. The resulting LVL displayed a higher strength and improved flame retardance, presenting modulus of rupture about 101 MPa, which was comparable to that of LVLs made by currently commercial adhesives. Simultaneously, these LVL boards remarkably suppressed the production of smoke and reduced the production of combustion heat, showing great potential in the application of the green architecture industry.